Role Supervisor To Formation Competence Professional Teacher - Hilmawarman, Hilman; Maunah, Binti; Mutohar, Prime Masrokan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Looking at the problematic conditions of a school institution in this millennial era, it can still be found that several teaching staff or teachers have problems and shortcomings in teaching activities in school institutions. This is related to a teaching method or system in the classroom and there are still many school institutions that still have low levels of human resources in teaching at these institutions. Of course, from this incident, a school institution requires supervisors to supervise teachers or develop guides, and motivate them so that the quality of teachers improves much better and makes them professional teaching staff. Thus, this research aims to answer questions regarding the role of supervisors in the formation of teachers' professional competence. This research uses qualitative research methods with a descriptive nature. The data collection used is documentation sourced from literature, articles, books, and other scientific papers that are relevant and related to the theme in the title. The data analysis technique is obtained through data reduction, data presentation, and conclusion. Meanwhile, the research results explain as follows: 1) The role of supervisor is needed by teachers to improve the quality of human resources in teaching in school institutions. 2) A teacher's professional skills as a teacher influence students' teaching and learning activities so that they can master learning in depth. 3) supervisors have a significant role in forming teachers' professional competence in teaching in a school institution.